Notch1 regulates tongue cancer cells proliferation, apoptosis and invasion. Issue 2 (17th January 2018) - Gan, Rui-Huan; Wei, Hua; Xie, Jing; Zheng, Dan-Ping; Luo, Er-Ling; Huang, Xiao-Yu; Xie, Jian; Zhao, Yong; Ding, Lin-Can; Su, Bo-Hua; Lin, Li-Song; Zheng, Da-Li; et al.
ABSTRACT: Objectives: Notch1 regulates tumor biology in a complex, context-dependent manner. The roles of Notch1 in tongue cancer are still controversial. The aim of this study is to investigate the roles of Notch1 in tongue cancer. Materials and Methods: The expression of Notch1 was tested between tongue cancer and normal samples by using immunohistochemistry. Tongue cancer cells were transfected with siRNA or plasmid, respectively. Cell proliferation, apoptosis, migration and invasion ability were tested in appropriate ways. The subcutaneous tumor model was established to observe the tumor growth. Results: Notch1 was upregulated in tongue carcinoma tissues and the expression of Notch1 was related with tumor stage and differentiation. Overexpression of Notch1 could increase tongue cancer cells proliferation, invasion and migration. But inhibited the expression of Notch1 could decrease cells proliferation, invasion and migration and promote cell apoptosis in vitro and in vivo . Conclusion: Our results prove that the oncogenic role of Notch1 in tongue cancer and provide the direction of targeted therapy of tongue cancer.